Farmer’s Lungs Disease: It’s Take A Breath Away! - Singh, Dolat; Soni, Sankar Lal; sharma, Vandana (Asian Journal of Pharmaceutical Research and Development, 2020)
Farmers were evaluated for the presence of farmer’s lung disease by serologic methods and by clinical histories. Farmer’s lung disease (FLD) is a form of hypersensitivity pneumonitis (HP) caused by inhaling microorganisms from hay or grain stored in conditions of high humidity in the agricultural workplace. The epidemiology of the disease is not well known, and is based on studies conducted by Central European and Asian groups. The clinical presentation may vary, differentiating the chronic (exposure to lower concentrations of the antigen over a longer period time) and the acute forms (after exposure to high concentrations of the antigen). It is more common in middle-aged men, although this probably reﬂects differences in exposure levels. It is also more common in non-smokers, probably because tobacco reduces the IgG response to inhaled antigens, affects cytokine production, and alters macrophage function. The etiology of the disease is clear - the inhalation of mouldy hay dust - and much can be done to prevent it ifthis is borne in mind. Mouldy hay dust is a very complex material consisting of innumerable fungal spores, hyphae and bacteria and fragments of vegetable matter. The treatment of FLD is based mainly on avoiding exposure to the antigen. This is the only measure that has been shown to delay disease progression. Corticosteroids are traditionally recommended in patients with impaired lung function and beta agonist and alpha blockers are also helpful in the treatment of disease.